Advancement of Gallium and Gallium-Based Compounds as Antimicrobial Agents - Li, Fupeng; Liu, Fengxiang; Huang, Kai; Yang, Shengbing (Frontiers in Bioengineering and Biotechnology, 2022)
With the abuse and misuse of antibiotics, antimicrobial resistance has become a challenging issue in the medical system. Iatrogenic and non-iatrogenic infections caused by multidrug-resistant (MDR) pathogens pose serious threats to global human life and health because the efficacy of traditional antibiotics has been greatly reduced and the resulting socio-economic burden has increased. It is important to find and develop non-antibiotic-dependent antibacterial strategies because the development of new antibiotics can hardly keep pace with the emergence of resistant bacteria. Gallium(Ⅲ) is a multi-target antibacterial agent that has an excellent antibacterial activity, especially against MDR pathogens; thus, a gallium(Ⅲ)-based treatment is expected to become a new antibacterial strategy. However, some limitations of gallium ions as antimicrobials still exist, including low bioavailability and explosive release. In recent years, with the development of nanomaterials and clathrates, the progress of manufacturing technology, and the emergence of synergistic antibacterial strategies, the antibacterial activities of gallium have greatly improved, and the scope of application in medical systems has expanded. This review summarizes the advancement of current optimization for these key factors. This review will enrich the knowledge about the efficiency and mechanism of various gallium-based antibacterial agents and provide strategies for the improvement of the antibacterial activity of gallium-based compounds.